Черный замок над озером: [роман] / Екатерина Островская - Островская Екатерина (Татьяна Устинова рекомендует, 2014)
Экземпляры: ф. 1 (20150330) / Инвентарный номер: 50120 / Цена: 145.00 / Авт.знак: О-77 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44